The Influence of Learning Agility Quotient, Intelligence Quotient, and Emotional Quotient on the Work Readiness of Accounting Education Students in the 4.0 Era - Anggraini, Lutfia; Sulastri, Sulastri (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2025)
This study aims to determine the influence of Learning Agility Quotient, Intelligence Quotient, and Emotional Quotient on the work readiness of Accounting Education students in the 4.0 era. The novelty of this research lies in integrating the Technology Acceptance Model (TAM) as a theoretical framework. TAM strengthens the understanding that work readiness in the 4.0 era is influenced by an individual's ability to accept and utilize technology, which is reflected in the aspects of LAQ, IQ, and EQ. The approach used in this research is explanatory quantitative, with data collected through questionnaires. The respondents of the study are Accounting Education students from the 2021 and 2022 cohorts at Universitas Negeri Malang. The sampling technique employed is simple random sampling, and the data analysis method used is multiple regression analysis. The research results indicate that LAQ, IQ, and EQ have a positive influence on work readiness, with a significance value.